Kvartérní amoniové soli - syntéza a využití - Padrtová, Tereza; Marvanová, Pavlína; Mokrý, Petr (Chemické listy, 2017)
Quaternary ammonium salts (QUATs) are compounds with wide use in organic synthesis, pharmacy or other fields of industry. Thanks to their specific physical and chemical properties resulting from their amphiphilic character they are already used as phase-transfer catalysts, ionic liquids, dyes, antimicrobial agents and disinfectants, antiarrhythmics, bronchodilators etc. There is still an effort to prepare new active compounds. Several organosynthetic methods are used to prepare QUATs: probably the best way is the Menshutkin reaction. Recently, also a microwave synthesis was introduced to prepare QUATs bringing better yields, shorter reaction times and a possibility of solvent-free reactions.
Keywords: antibakteriální látky; kvartérní amoniové sloučeniny; Quaternary Ammonium Compounds; alkylace; Drug Resistance, Bacterial; Alkylation; Anti-Bacterial Agents; bakteriální léková rezistence